Increasing levels of saliva alpha amylase in electrohypersensitive (EHS) patients. (3rd August 2017) - Andrianome, Soafara; Hugueville, Laurent; de Seze, René; Selmaoui, Brahim
Abstract: Purpose: To assess the level of various salivary and urinary markers of patients with electromagnetic hypersensitivity (EHS) and to compare them with those of a healthy control group. Materials and methods: We analyzed samples from 30 EHS individuals and a matched control group of 25 individuals (non-EHS) aged between 22 and 66. We quantified cortisol both in saliva and urine, alpha amylase (sAA), immunoglobulin A and C Reactive Protein levels in saliva and neopterin in urine (uNeopterin). Results: sAA was found to be significantly higher ( p  < 0.005) in the EHS group. uNeopterin and sAA analysis showed a significant difference based on the duration of EHS. Conclusion: Higher levels of sAA in EHS participants may suggest that the sympathetic adrenal medullar system is activated. However, most of the analyzed markers of the immune system, sympathetic activity and circadian rhythm did not vary significantly in the EHS group. There is a trend to the higher levels of some variables in subgroups according to the EHS duration.